Catalano mobili: the price of change - Catalano, Antonio (2017)
The following case study aims to introduce and analyse real-life challenges that Catalano Mobili, a family furniture business, faced after a non-family manager was introduced and the familial instability prompted as a direct result of the outside hire. Conversely, the case intends to illustrate the struggles commonly associated with being a nonfamily manager in a small family business, and to illustrate the complex nature of having to make decisions in a nonfamily managerial capacity in the context of blurred boundaries between the business and the family. The teaching note is provided in order to analyse the case from a theoretic point of view.